AN ANALYSIS ON EMPHATIC LISTENING STYLE IN EFL CLASSROOM - Arief, Mardhatillah; Syatriana, Eny; Hamid, Sitti Maryam (FKIP Unismuh Makassar, 2023)
The objectives of this research are: (1) To explore the styles of empathic listening skill used by EFL teacher in the classroom at SMP Negeri 4 Majauleng; (2) To determine EFL students’ perceptions toward empathic listening skill in the classroom at SMP Negeri 4 Majauleng. This study employed a qualitative research methodology. The researcher used a qualitative method, observing classrooms through video and audio recording, documentation, and interviews with teachers and students. The subject of the research was 20 students from one class who have participated in emphatic learning activities and assessed their views of emphatic listening in the learning activity SMP Negeri 4 Majauleng. The instrument of the research used observationand Interview. The Result of the research show that EFL teacher of SMP Negeri 4 Majauleng applied five empathic listening styles, they are questioning, advising, judging, analyzing and supporting. The students gave positive perception toward the used of empathic listening skill by the teacher in the classroom due to the fact that the emphatic listening gave good influence to the listening skill of the students.